Contemporary Accounting - Bazley, Mike (Melbourne Thomson, 2004)
The inclusion throughout the text of current and relevant newspaper articles, along with the 2002 Woolworths annual report, will assist students to relate their study to the real-world business environment. Australian authors Fifth edition of bestselling Australian text.
Age Group: Adult
Previous ed. : 2001.
Includes index.
Keywords: Accounting -- Australia -- Textbooks